A Systematic Review on the Association Between Vestibular Dysfunction and Balance Performance in Children With Hearing Loss. Issue 3 (28th September 2021) - Singh, Anisha; Heet, Hannah; Guggenheim, Dana S.; Lim, Margaret; Garg, Bhavika; Bao, Matthew; Smith, Sherri L.; Garrison, Doug; Raynor, Eileen M.; Lee, Janet W.; Wrigley, Jordan; Riska, Kristal M.
Abstract : Objectives: The objective of this study was to understand the functional impact of vestibular dysfunction on balance control in children with hearing loss. The vestibular system is an important contributor to maintaining balance. In adults, vestibular dysfunction is known to lead to unsteadiness and falls. Considerably less is known about the effects of vestibular dysfunction in children with hearing loss. Design: We conducted a systematic review in concordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. We included articles on children with hearing loss who underwent vestibular and balance testing. The Downs and Black checklist was used to assess the risk of bias. Results: A total of 20 articles were included in this systematic review, of which, 17 reported an association between vestibular dysfunction and balance abnormalities in children with hearing loss. Bias (as measured by the Downs and Black Checklist) was a concern, as most studies were nonblinded cohort studies or case series selected through convenience sampling. Conclusions: Research to date has predominantly found that children with concomitant hearing loss and vestibular impairment tend to perform more poorly on balance measures than either children with hearing loss and normal vestibular function or children with both normal-hearing and normal vestibular function. A standardized approach to assessing both vestibular function and balance would better characterize the impact of vestibular dysfunction in children with hearing loss at the population level.